Nutrient Management Drives the Direction and Magnitude of Nitrous Oxide Flux in Crop Residue-Returned Soil Under Different Soil Moisture - Lenka, Sangeeta; Choudhary, Rajesh; Lenka, Narendra Kumar; Saha, Jayant Kumar; Amat, Dolamani; Patra, Ashok Kumar; Gami, Vijay; Singh, Dharmendra (Frontiers in Environmental Science, 2022)
Crop residues as key organic carbon inputs have the potential for soil carbon sequestration. However, previous studies have shown an inconsistent effect of residue return on the direction and magnitude of soil nitrous oxide (N2O) emission. We used a laboratory-based soil incubation study to test the response of N2O emission to crop residue type, soil moisture, and how nutrient management modulates these responses. In this study, we incorporated crop residues with different qualities (wheat, rice, soybean, and maize) at two soil moisture contents 80% field capacity (FC) and 60% FC and under seven nutrient levels: N0P0K0 (no nutrients), N0PK, N100PK, N150PK, N100PK + manure@ 5 Mg ha−1, N100PK + biochar@ 5 Mg ha−1, and N150PK + biochar@ 5 Mg ha−1. The results demonstrated significant (p < 0.01) differences in the magnitude of N2O emissions among treatments. However, only the interaction effect of residue × nutrient and nutrient × moisture was significant (p < 0.05). N100PK and N150PK at 80% FC mitigated N2O emission by approximately 20% in wheat residue-amended soil (cf. control soil without residue). In contrast, maize residue amendment (cf. control soil) increased N2O emission by 130% under N0P0K0 and 80% FC. Residue effects were negatively correlated with the C:N ratio, and a strong positive correlation (p < 0.01) was obtained between N2O emission and CO2 respiration, labile carbon, mineral N, and residue total nitrogen (TN). When no nutrients were added, N2O emission was higher in residue returned soil. However, cumulative fluxes of N2O decreased by 6–17% when maize and wheat residues (cf. control soil) were applied with nutrients. Negative fluxes of N2O indicating consumption were observed in every treatment after 57 days of incubation and were most pronounced in control soil without residue and nutrients. Decreasing the soil moisture from 80% FC to 60% FC, the N2O consumption rate increased by 6.6 times across residue types and nutrient management. The regression analysis and structural equation modeling (SEM) results showed that residue TN, soil CO2 emission, NO3-N, and labile SOC were the key predictor variables and could explain 82% variability in the soil N2O emission in the Vertisols of Central India. The results suggested that nutrient addition (NPK) could alter the magnitude and direction of soil N2O flux by residue type and soil moisture by influencing the underlying soil microbial processes of the C and N cycle in the Vertisol of subtropical India.